Răspuns :
[tex]a = - 2[/tex]
[tex] - a = - ( - 2) = 2[/tex]
[tex] \frac{1}{a} = \frac{1}{ - 2} = - \frac{1}{2} [/tex]
[tex] - a + \frac{1}{a} = 2 + ( - \frac{1}{2} ) = 2 - \frac{1}{2} = \frac{4}{2} - \frac{1}{2} = \frac{4 - 1}{2} = \frac{3}{2} [/tex]
[tex] - a = - ( - 2) = 2[/tex]
[tex] \frac{1}{a} = \frac{1}{ - 2} = - \frac{1}{2} [/tex]
[tex] - a + \frac{1}{a} = 2 + ( - \frac{1}{2} ) = 2 - \frac{1}{2} = \frac{4}{2} - \frac{1}{2} = \frac{4 - 1}{2} = \frac{3}{2} [/tex]
Știm că:
opusul lui a = -a => (-2)=2
inversul lui a = 1 => -1
a 2
2+(-1) = 4 - 1 = 3
2 2 2 2